Sustainability and friendly circulation path in Sangiran museum, Sragen Indonesia - Hanendya, Seruni Inas; Syamsiyah, Nur Rahmawati (Applied Research and Smart Technology (ARSTech), 2021)
Museums are windows into a country's past. Museums can tell stories about history and life. Sangiran museum is one of the world's heritages that tell the story of human evolution from prehistoric times to the present. The presence of historical or other information in the museum heavily relies on the zoning of space and circulation paths. The circulation of visitor movements between spaces and buildings significantly impacts the museum's function. Submission of historical information to visitors will be easier to understand if there is good circulation, which supports visitor movement activities. In the observations, the movement of visitors at the Sangiran museum has constructed an uncomfortable feeling for the users. This study aims to assess the circulation path's compliance with government standards. Due to the nature of this study, a descriptive qualitative approach is required. The study discovered three types of circulation paths that were not user-friendly, namely ram, stairs, and hallways. They did not meet Indonesian government and international data architecture standards. Hence, this study proposes an easy-to-implement design to ensure the long-term function and sustainability of the circulation pathway.